A compact decagonal‐shaped UWB monopole planar antenna with truncated ground plane. Issue 12 (30th October 2018) - Ali, Tanweer; Subhash, B. K.; Pathan, Sameena; Biradar, Rajashekhar C.
Abstract: A compact (35 × 35 × 1.6 mm 3 ) decagonal shaped ultrawideband (UWB) antenna that gives wide impedance bandwidth of >139% (2.3‐12.8 GHz), 1.7‐5 dBi gain, good time domain characteristics and average efficiency >88% is proposed. UWB operation in the proposed design is accomplished by using truncation at the ground plane. Simulated results are in good agreement with the measured results.